ANALYZING CONSUMERS’ PERCEPTION OF THE USE OF ELECTRONIC PAYMENT IN MANADO - Tuilan, Brenda Melania; Pangemanan, Sifrid S.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Electronic payment system has grown rapidly in recent years especially in Indonesia. This e-payment system has substituted the role of money as a tool to transact. It is seen from many new products of e-payment are emerging in the form of card-based and application based. The presence of e-payment transaction provides many conveniences and advantages for the consumer as well as the business community. Therefore, this study aims to analyze consumers’ perception of the use of electronic payment in Manado. To achieve this objective, the researcher obtained information from 20 informants used a qualitative study which is semi-structured interview to get detailed results. The results of this study showed factors; perceived trust, perceived usefulness, perceived ease of use, security and attitude have significant influence to consumer to use e-payment. Those factors sufficiently showed positive response towards its usage. Consumers dominantly have high trust and good perception with the security as well as the usefulness and ease of use of e-payment usage. However, this study indicated, network or system error become the main problem that faced by consumers during transaction. For issuer, it is better to keep improving the service quality, the security system as well as the infrastructure in Manado. Keywords: consumers perception, electronic payment, perceived trust, perceived usefulness, perceived ease of use, security,  attitude.